Readiness Of University Students In Special Education To Work With Pupils With Special Educational Needs In The Inclusive Education System - Tzvetkova-Arsova, Mira; Tomova, Margarita
This paper presents the results from a questionnaire among 32 university students in special education on bachelor level at Sofia University Saint Kliment Ohridski in Bulgaria, who are in their final year of education, about their readiness for future work with pupils with special educational needs in inclusive settings. The level of the students’ theoretical and practical preparation is studied, as well as specific aspects of their acquired knowledge and experience in fields like Braille, sign language, alternative and augmentative communication (AAC) etc.
Keywords: Inclusive education; Special education